Potret Ideal Sikap Moderat Kiai di Era Millenial - Muhammad Idlom Dzulqarnain (JASNA : Journal For Aswaja Studies, 2021)
AbstractThe problem of the breakdown of unity is a latent problem as well as a threat to the integrity of the nation. Ideological  divisions  and  conflicts  do  not  occur  between  religions,  races,  or  groups.Splits  and disintegration are also vulnerable to occur between religious leaders or kiai, andalsobetween students. Starting  from the result  of  blind fanaticism,  old-fashioned thinking,  and  lack  of  awareness  of  tolerance. Therefore, there needs to be an awareness of the kiai to be moderate. Because the kiai's thoughts have a lot of influence on theirstudents. This study aimedto analyze how the indicators of moderate, as well as the ideal portrait of the moderate attitude of the kiai. This study usedqualitative methods and descriptive analysis.  The  results  of  the  study  show  that  several  indicators  of  moderate  kiai  can  be  mapped  on  four aspects. Firstly, the aspect of aqidah or ideology. The kiai in using arguments need to be balanced between naqli arguments and aqli arguments, so it is not easy to judge others wrong. Secondly, the social aspect. The  kiai  need  to  get  along  with  all  groups,  prioritize  common  affairs,  and  peace.  Thirdly,  the  cultural aspect. Kiai need to emphasize prevention rather than punishment with violence, democracyand get used to a culture of deliberation in deciding cases. A culture of tolerance while maintaining good old culture or methods,  and  remaining  open  to  newness  or  technology.  Fourthly,  the  national  aspect.  Kiai  need  to maintain the existence of national unity by upholding tolerance, respecting and obeying the government as long as it does not deviate from norms and religion, expresses opinions or criticisms to the authorities in a wise manner without violence.Keywords: kiai, moderation, pesantrenAbstrakProblem  pecahnya  persatuan  menjadi  masalah  laten sekaligus ancaman keutuhan bangsa.  Perpecahan dan  konflik ideologi tidak  hanya  terjadi  antar  agama,  ras,  atau  kelompok.  Perpecahan  dan  disintegrasi juga  rentan  terjadi  antar  pemuka  agama  atau  kiai,  dan  antar  santri.  Mulai  dari  akibat  fanatisme  buta, pemikiran yang kolot, dan kurangnya kesadaran toleransi. Oleh karena itu perlu ada kesadaran kiai untuk bersikap  moderat. Karena pemikiran  kiai  memiliki  banyak  pengaruh  terhadap  para  santri.  Tujuan penelitian  ini  untuk  menganalisis  bagaimana  indikator  moderat,  serta  potret  ideal sikap  moderat kiai. Penelitian  ini  menggunakan  metode kualitatif  dan  analisis  deskriptif. Hasil  penelitian  menujukkan beberapa inidikator moderat kiai dapat dipetakan pada empat aspek. Pertama, aspek aqidah atau ideologi.  Para kiai dalam menggunakan dalil perlu seimbang antara dalil naqli maupun dalil aqli,sehingga tidak mudah memvonis orang lain salah. Kedua, aspeksosial. Para kiai perlu bergaul dengan semua golongan, mengutamakan urusan bersama, dan perdamaian. Ketiga, aspek budaya. Kiai perlu menekankan preventif dari pada  punishment  dengan kekerasan, demokratis  dan  membiasakan  budaya  musyawarah  dalam memutuskan perkara. Budaya toleransi dengan tetap menjaga budaya atau metode lama yang baik, dan tetap terbuka dengan kebaruan atau teknologi. Keempat, aspek kebangsaan. Kiai perlu menjaga eksistensi kesatuan bangsa dengan menjunjung sikap toleransi, menghormati serta menaati pemerintah selama tidak menyimpang dari norma dan agama, menyampaikan pendapat atau kritik kepada penguasa dengan cara bijak tanpa kekerasan.Kata Kunci: kiai, moderat, pesantren